Downregulation of MHC class I expression due to interference with p105-NF kappa B1 processing by Ad12E1A. - Schouten, G J (1995)
We have previously demonstrated that expression of major histocompatibility complex (MHC) class I genes is repressed in baby rat kidney cells transformed by early region 1 of oncogenic adenovirus type 12 (Ad12E1). Reduced expression of MHC class I antigens contributes to the escape of Ad12-transformed cells from T-cell-mediated immune surveillance and to tumour induction. In this study, we show that repression of MHC class I expression by Ad12E1A is mediated via the H2TF1 element of the MHC class I promoter. This element binds NF kappa B and KBF1, two factors which play a major role in the regulation of MHC class I expression in vivo. In extracts from Ad12E1-transformed cells, binding of KBF1 and NF kappa B to the H2TF1 element is decreased. This is caused by reduced production of p50-NF kappa B1, the 50 kDa subunit shared by KBF1 and NF kappa B, due to interference with p105-NF kappa B1 processing by Ad12-13S-E1A protein. Overexpression of the p105-NF kappa B1 cDNA, or of a truncated p105-NF kappa B1 cDNA that codes for p50-NF kappa B1, restores MHC class I expression in Ad12E1-transformed cells. These data demonstrate that downregulation of MHC class I expression in Ad12E1-transformed cells is due to interference with processing of p105-NF kappa B1 by the Ad12-13S-E1A protein.